Investigation of The Relationship Between Healthy Life Style Behaviors and Body Mass Index of Universıty Students - Ramazan Bayer; Serkan Düz; Rabia Hürrem Özdurak Sıngın (Türk Spor ve Egzersiz Dergisi)
Aim: Obesity, which is one of the most important health problems of our age, affects many people of all ages and genders in our country. Particularly, the irregular eating habits of students, their orientation towards fast-foods and their sedentary lives are some of the reasons that trigger obesity disorder. For this reason, this issue has been given more importance for people to get rid of obesity and lead a healthy life. This study was carried out to determine the relationship between healthy lifestyle behaviors and body mass index of university students. Method: The sample of the study consisted of 632 students studying at Inonu University in the 2017-2018 academic year. A 20-question personal information form, anthropometric measurements and Healthy Lifestyle Scale (HLSS) were used as data collection tools. The data obtained were analyzed using independent sample t-test, Mann Whitney-U test, one-way Analysis of Variance and Kruskal Wallis-H test. Results: The most important finding of the study is that inadequate physical activity and irregular dietary habits affect stress level of the students. Moreover, when the relationship between the body mass index (BMI) and HLSS sub-dimensions of university students was analyzed, it was determined that there was a statistically significant difference among BMI and sub-dimensions of dietary habits and health responsibility. Conclusion: In order to be healthy individuals, a sedentary lifestyle should be avoided, regular and balanced diet should be taken care of and fast-food type dietary habits should reduced or stopped.